Antithrombotic Strategies in Perioperative Period - Hasan, Md Nazmul; Siddique, Md Abu; Banerjee, Sajal Krishna; Ahsan, Syed Ali; Rahman, AKM Fazlur; Ahmed, Choudhury Meshkat; Kabir, Mohammad Faisal Ibn; Hoque, Md Harisul (University Heart Journal, 2014)
Antithrombotic therapy (Warfarin, Aspirin,Clopidogrel etc.) are routinely used in prevention and treatment of various cardiovascular diseases. In patients who are having a surgical or other invasive procedure, interruption of antithrombotic therapy is typically required to minimize the risk for perioperative bleeding. It involves balancing the risk of periprocedural bleeding with continued treatment against the thrombotic risk with suspension of treatment and use of bridging anticoagulation therapy. The need for bridging is driven by patients estimated risk for thromboembolism and the bleeding risk of invasive procedure. Treatment with subcutaneous low-molecular- weight heparin or intravenous unfractionated heparin at a therapeutic dose before and after the procedure recommended as bridging anticoagulation therapy. DOI: http://dx.doi.org/10.3329/uhj.v9i1.19511 University Heart Journal Vol. 9, No. 1, January 2013; 47-51